ETIKA POLITIK IDENTITAS DALAM PERSPEKTIF ‘AṢABIYYAH IBN KHALDUN - Muhammad Agus Awalus Shoim; Muhammad Syamsul Arif (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2025)
Oppressive power arises from the absence of political ethics. In a democratic system, power originates from the people’s support; therefore, when it turns oppressive, it contradicts the fundamental principles of democracy. Alongside oppression, identity politics emerges as a double-edged phenomenon—promoting social solidarity while potentially leading to social fragmentation. This study examines the relationship between power, ethics, and identity politics from the perspective of Ibn Khaldun’s thought to uncover a philosophical foundation for the development of political ethics within the Islamic context. The research is qualitative in nature, employing a descriptive-analytical method and adopting Émile Durkheim’s theory of social solidarity and Max Weber’s theory of traditional authority as its analytical approaches. Through a literature-based examination of primary and secondary sources, this study analyzes how Ibn Khaldun’s concept of ‘aṣabiyyah explains the interconnection between power, ethics, and social order. The findings show that power grounded in ethics generates constructive social relations. Political aims oriented toward the acquisition of power remain legitimate as long as they are guided by ethical principles. Furthermore, identity politics can foster positive social cohesion when rooted in rationality, morality, and social order, as reflected in Ibn Khaldun’s social philosophy.